2009
DOI: 10.1002/ca.20833
|View full text |Cite
|
Sign up to set email alerts
|

A survey of medical students on the impact of a new digital imaging library in the dissection room

Abstract: Radiology has a recognised role in undergraduate anatomy education. The recent digitalisation of radiology has created new learning opportunities involving techniques such as image labelling, 3D reconstruction, and multiplanar reformatting. An opportunity was identified at the University of Nottingham to create a digital library of normal radiology images as a learner-driven adjunct in anatomy dissection sessions. We describe the process of creating a de novo digital library by sourcing images for presentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 7 publications
3
32
0
1
Order By: Relevance
“…In this respect, digital resources are becoming an important part of health education (Schultze-Mosgau et al, 2004;Beux & Fieschi, 2007;Chen et al, 2008;Turmezei, 2009;Silva et al, 2011). It is therefore expected that the inclusion of these resources in the study of morphological sciences will facilitate access to practical contents involved in distance learning in order to extend the benefits to different education sectors of the society.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, digital resources are becoming an important part of health education (Schultze-Mosgau et al, 2004;Beux & Fieschi, 2007;Chen et al, 2008;Turmezei, 2009;Silva et al, 2011). It is therefore expected that the inclusion of these resources in the study of morphological sciences will facilitate access to practical contents involved in distance learning in order to extend the benefits to different education sectors of the society.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of radiology basics and new learning opportunities involving such techniques as image labelling, 3D reconstruction, and multiplanar reformatting appear to be relevant [48]. The virtual human dissector or the 3D stereoscopic images are significant elements of the modern anatomical curriculum making the study of anatomy more effective [12,16,35,40].…”
Section: Category 3 Other (Problem-based Learning and Visualisation)mentioning
confidence: 99%
“…In a previous study that provided passive access to radiographic imaging during dissection, students reported that direct instruction and additional labeling would further potentiate the use of radiographic imaging in the anatomy laboratory (Turmezei et al 2009). In addition, there is a long-held belief and evidence that mental rotation ability and spatial reasoning are necessary for both radiologic and gross anatomical comprehension (Squire 1969;Squire et al 1975;Folan & de Montfort Supple 1986;Terrell 2006;Khalil et al 2008).…”
Section: Exam Performancementioning
confidence: 99%
“…The most commonly reported methods to incorporate radiology with anatomy instruction include concurrent radiology lectures (Sullivan et al 1987;Squire 1989;Erkonen et al 1992), small group learning with (Forrester 1971) and without (Tegtmeyer et al 1974;Whitley 1977) formal instructors, and radiologic images of de-identified patients in the dissection laboratory (Squire et al 1975;Reidy et al 1978;Bassett & Squire 1985;Turmezei et al 2009). Others include problembased learning (Navsa et al 2004;Subramaniam et al 2004;Subramaniam 2006), ultrasound workshops using students and human models (Teichgraber et al 1996;Wittich et al 2002), and radiologic imaging of dissection laboratory cadavers (McNiesh et al 1983;Hisley et al 2008).…”
Section: Introductionmentioning
confidence: 99%